Effect of Glycerin Content as Plasticizer in the Preparation of Cassava Plastic and Seed (Capseed) - Asyifa C.A; Labibah D.N; Nabila D; Yasmin K; Bilqiz K.M (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan